Facile synthesis of highly stable BF3-induced meso-tetrakis (4-sulfonato phenyl) porphyrin (TPPS4)-J-aggregates: structure, photophysical and electrochemical properties - Venkatramaiah, N.
We report herein, a novel method for the formation of highly stable BF3-induced J-aggregates by interaction between meso-tetrakis(4-sulfonatophenyl) porphyrin (TPPS4) and BF3O(C2H5)(2). The aggregates were characterized by NMR (H-1, B-11 and F-19), optical absorption, cyclic voltammetry, FT-IR and fluorescence spectroscopic techniques. TPPS4 readily forms a 1 : 2 adduct with BF3 which further converts into BF3-induced TPPS4 aggregates whose spectroscopic properties strongly depend on the concentration of BF3. The optical absorption spectrum shows the formation of J-type aggregates with an apparent association constant (logK(app)) of 4.2 +/- 0.1. The steady state emission shows formation of 1 : 2 (TPPS4-BF3) adducts at similar to 685 nm and J-aggregates exhibit emission at 732 nm with a red shift of similar to 17 nm in comparison to J-aggregates of TPPS4 with TFA. The fluorescence lifetime of TPPS4 : BF3 (1 : 2) adducts exhibits similar to 3.68 ns and aggregates show a lifetime of 4.32 +/- 0.2 ns with major abundance. NMR study reveals that proton transfer occurs from pyrrole N-H to the SO3- groups and J-aggregates were stabilized by strong intermolecular hydrogen bonding interaction between N-2-BF2 and SO3H. Cyclic voltammetry shows a decrease in the reduction peak current along with a change in the peak potentials for the aggregates. The PXRD pattern of the aggregates exhibits orthorhombic structure with interplanar distance of 4.87 angstrom. The variations in unusual stability, photophysical, electrochemical properties and nature of the aggregates were rationalized with aggregates of TPPS4 dication.